BIOACTIVITY SCREENING OF SELECTED TRADITIONAL MEDICINAL PLANTS OF KERALA - Alphons Baby, Alby; Raphael K, Regi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Traditional medicines all over the world is revaluing nowadays by extensive research programs. To validate the traditional use, the active components in them need to be identified, characterized, and biologically evaluated. Stereospermum suaveolens, Hygrophila spinosa, and Naravelia zeylanica are important medicinal plants used by the ethnic people of Kerala against various ailments. The present study validates the ethnomedical uses of S. suaveolens, H. spinosa, and N. zeylanica by screening their antimicrobial, anthelmintic, and antioxidant properties. Method: All the analyses were done according to standard protocols. Results: The ethanolic extracts of their useful parts were investigated for antimicrobial activity against 10 human pathogenic microorganisms. All the three plants had shown prominent antimicrobial activities, and S. suaveolens exhibits comparatively more antifungal activity in their higher concentration (500 Î¼g/mL). Anthelmintic efficiency of the plants was screened using Indian adult earthworm Pheretima posthuma. All of them had shown significant activity, and the highest was observed in S. suaveolens leaves. Antioxidant potential of the plants was screened using 2,2 diphenyl 1-picrylhydrazyl (DPPH) free radical scavenging assay and superoxide anion scavenging assay. In DPPH free radical scavenging assay, maximum radical scavenging was shown by S. suaveolens with IC50 value 61.6Â±2.3 Î¼g/mL, and in superoxide anion scavenging assay, maximum activity was in N. zeylanica with IC50 value of 74.66Â±8.5 Î¼g/mL. Conclusion: This study provides scientific evidence on the traditional use of S. suaveolens (leaves), H. spinosa (leaves), and N. zeylanica (aerial part) in treating microbial diseases, worm disturbances, and their potential as an antioxidant agent.